PROTECTIVE EFFECTS OF GINGER (Zingiber officinale) EXTRACT AGAINST LEAD INDUCED OXIDATIVE STRESS ON LIVER ANTIOXIDANT ENZYMES IN MALE ALBINO RATS - M.PRATAP; P.INDIRA (International Journal of Pharma and Bio Sciences, 2014)
In the present study, ethanolic extract of ginger on lead acetate induced toxicity was studied in male wistar albino rats. Seven groups of rats were used in the study. Glutathione peroxidase, Glutathione reductase, Glutathione-S-transferase, Catalase and Superoxide dismutase were decreased in lead acetate treated (200mg/kg body weight, once daily for eight weeks) group. However treatment with ethanolic extract of gingerI(200mg/kg body weight, once daily for eight weeks) and ginger-II(300mg/kg body weight, once daily for eight weeks) these parameters came to normal showing the antioxidant effect of ginger. The antioxidant effects of ginger may modulate the oxidative stress parameters. The results confirm the hepato protective effects of ginger in lead acetate treated rats.